Strategi Kepala Madrasah Dalam Merealisasikan Profil Pelajar Pancasila Di Madrasah Tsanawiyah Miftahul Ulum Sukodono Lumajang - Khoirotun Nisak; Dani Hermawan (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2023)
This research is motivated by the rampant moral degradation that often occurs today. Moral problems can be said to be very natural to accompany human life. This happens due to their lack of understanding of the values ​​contained in Pancasila so that not a few of them commit deviant acts such as brawls, bullying, promiscuity, violating school rules, being brave towards teachers, and so on. The aims of this research are: 1 ) To describe how the principal's strategy in realizing the profile of Pancasila students at Madrasah Tsanawiyah Miftahul Ulum Sukodono Lumajang. 2) To describe the supporting and inhibiting factors of the madrasa principal's strategy in realizing the profile of Pancasila students at Madrasah Tsanawiyah Miftahul Ulum Sukodono Lumajang. This research uses descriptive qualitative research with a case study type. The results of this study are 1) the strategy of the madrasa head in realizing the Pancasila student profile by conducting environmental observations, formulating strategies, implementing strategies, and evaluating. In addition, Pancasila values ​​have also been implemented in madrasas such as carrying out the habit of praying midday prayers in congregation, reading juz ammah, reading istighotsah, reading rotibul hadad, reading Yasin letters, and reading asmaul husna before learning begins, carrying out flag ceremonies every Monday and respecting each other. fellow friends, community service at school, aware of their independent obligations as students by working on their exam questions, active in organizational activities, and able to think creatively in learning by making infographics in class. 2) supporting factors include good cooperation between madrasa heads and teaching staff, adequate infrastructure, and full participation of madrasa residents. While the inhibiting factors are family background and environmental influences outside the madrasah.